Readiness Before Adoption: Exploring AI Integration in Egyptian Nonprofit Fundraising - Zayed, Marwa Y (AUC Knowledge Fountain, 2026)
Abstract Artificial intelligence (AI) has been transforming fundraising through data-driven decision-making, automation, and personalized donor engagement. Existing research focuses on AI applications and outcomes in the nonprofit sector in western context, with little known information in the Global South, particularly Egypt. This gap makes understanding the organizational conditions that shape AI difficult and limited. This thesis examines how organizational, cultural, ethical, and resource-related factors shape Egyptian nonprofit organizations’ readiness to adopt AI in fundraising. Through a qualitative approach, semi-structured interviews were conducted with 21 fundraising directors, CEOs, a governmental representative, and technology professionals working in Egyptian nonprofits based in Cairo across diverse missions. The data were analyzed thematically to capture the real perceptions. The findings showed that while the participants express curiosity and interest toward AI, the Egyptian nonprofit remains in a pre-adoption stage. Individual fundraisers use generative AI tools, mostly the free versions informally, without organizational support or the existence of clear governance and data protection structured frameworks. Five main forces shape the readiness of Egyptian nonprofits' fundraising, indicating that adoption is constrained by psychological readiness and resistance, tensions between innovation and human-centered fundraising, digital capabilities and human capital gaps, data ethics and governance concerns, and financial and competitive pressures, and not by resistance to innovation. They interact altogether, limiting nonprofits’ ability to adoption phase.  If these readiness factors are mitigated, it may lead to the potential adoption of AI in Egyptian fundraising. AI adoption in fundraising is less shaped by technology and more by organizational readiness, governance, leadership alignment, investment in human capital, and AI literacy.